Barcoding Amino Acids for Mutation Screening in Amyloid Beta Peptides. Issue 11 (3rd October 2019) - Hoang, Phuong; Khashab, Niveen M.
Abstract: Amino acid (AA) substitutions are directly correlated with specific pathologies such as Alzheimer's disease, making their rapid screening and detection critical to treatment and scientific study. A proof‐of‐concept implementation of the label‐free and noninvasive Raman spectroscopy technique for the detection of AA substitutions in primary peptide fragments is demonstrated. By encoding the Raman "fingerprint" of individual AAs into binary formats called optical identification tags (OITs), a library of identifiers is created, which can then be used for detecting mutations. When the recorded Raman signal is enhanced by using surface‐enhanced Raman scattering substrate, the mutation screening strategy can detect a single point missense mutation in an 11‐AA peptide fragment of amyloid beta Aβ(25–35) and a frameshift mutation in a 42‐AA fragment Aβ(1–42) down to picomolar concentrations. The combination of high sensitivity and simple operation makes the use of OITs a promising approach for high‐throughput automated screening. Abstract : A label‐free and high‐throughput automated screening of amino acid mutation in peptide chains without sample destruction is proposed. Raman fingerprint of every individual amino acid is converted into a binary optical identification tag and is further amplified by using the provided surface‐enhanced Raman scattering substrate, which allows detecting a mutation point in peptide down to picomolar concentrations.